PERSONALIZED INTENSIVE CARE OF CARDIOVASCULAR DISORDERS IN CHILDREN WITH RESPIRATORY FAILURE - Filyk, Olha (The Ukrainian Scientific Medical Youth Journal, 2020)
This article presents data on the frequency of incidence and duration of cardiovascular dysfunction in children with acute respiratory failure. The information on expediency of carrying out of personalized hemodynamic management in case of its insufficiency with use of multiparametric approach to estimate haemodynamic data are presented. The aim of the study was to compare the effectiveness of the standard approach and proposed by us additions to treatment of haemodynamic disorders in children with respiratory failure. It was summarized from the literature reviews that the presence and maintenance of patient`s spontaneous breathing pattern with use of non-invasive estimated cardiovascular monitoring, evaluation of preload with ultrasonography and reassessment of rate and volume of fluid replacement with taking into account solution`s composition might improve treatment results in children with acute respiratory failure. We conducted a prospective single-center non-interventional cohort study in children with acute respiratory failure 1 month - 18 years old. Patients were randomly divided into I and II groups. The data analysis included 43 patients of group I, who received conventional for this intensive care unit monitoring and treatment and 53 patients of group II, in whom we took into account the results of multiparametric monitoring during the correction of hemodynamics.Monitoring of hemodynamics included heart rate, non-invasive systolic, diastolic and mean blood pressure capillary refill time and presence of peripheral arteries pulsation with clinical verification of "warm" or "cold" shock, ScvO2 and lactate levels in the central venous blood; non-invasive estimated monitoring of stroke volume, cardiac output, cardiac index, stroke index using the esCCO technology, NIHON COHDEN (Japan) and the ratio of inferior vena cava diameter at inspiration and exhalation. Hemodynamic support in groups I and II included early goal-directad therapy, individualized and personalized treatment. In II group of patients there were taken into account the dynamics of changes of non-invasive esCCO data about stroke volume, cardiac output, cardiac index and stroke index, cumulative hydrobalance and the ratio of the of inferior vena cava diameter at inspiration and exhalation. Early goal-directed therapy was aimed to (supra) normalize of blood flow and was based on normal hemodynamic data for population, according to percentiles for specific age groups of patients. Individualized hemodynamic therapy included functional hemodynamic monitoring with assessment of to volemic therapy answer, individualization of target points and maximization of blood flow. Personalized hemodynamic management consisted of applying an adaptive multiparametric approach to hemodynamic assessment. Spontaneous diaphragmatic activity was maintained along all time of mechanical ventilation. The primary endpoint was 28-day mortality rate; secondary endpoints were the duration of cardiovascular dysfunction and the duration of intensive care unit stay. To assess age-dependent data, patients were divided into age subgroups: 1st subgroup - children 1 month - 1 year old; 2nd subgroup - children 1 - 3 years old; 3rd subgroup - children 3 - 6 years old; 4th subgroup - children 6 - 12 years old; 5th subgroup - children 12 - 18 years old. It was determined that the level of 28-day mortality was: in 1st age subgroup - 18.2% in group I and 3.1% in group II (p = 0.02), in the 2nd age subgroup - 11.1% and 0%, respectively (p = 0.11); in the 4th age subgroup - 10% and 0%, respectively (p = 0.28); in the 3rd and 5th age subgroups - was 0% in I and II groups. The prevalence of hemodynamic disorders was: in 1st age subgroup in patients of group I - 100%, while in group II - 62.5% (p = 0.001); in 2nd age subgroup - 55.6% in patients from group I and 42.9% in patients from group II (p = 0.05); in 3rd age subgroup in 100% of patients of group II and only in 75% of patients of group I (p = 0.02). In the 4th age subgroup no significant differences were found between I (30% of patients) and II groups (25% of patients), p = 0.28; in 5th age subgroup the frequency of cardiovascular dysfunction was 40% in group I, compared with 75% in group II (p = 0.008). It was found that duration of hemodynamic insufficiency was longer in patients of 1st and 4th age subgroups, and relatively shorter in patients of 5th age subgroup: in the 1st age subgroup it was 7.6 ± 0.5 days in group I and 8.8 ± 0.9 days in group II (p> 0.05); in 4th age subgroup - 6.7 ± 0.4 days in group I and 10.1 ± 1.2 days in group II (p> 0.05), while in 5th age subgroup - 4.1 ± 0.3 days in group I and 4.7 ± 0.5 days in group II (p> 0.05). We found that there were significant differences in the duration of stay in intensive care unit among patients of the 1st and 5th age subgroups. Specifically, in 1st age subgroup this indicator was in 1.3 times less in group II, compared with group I (p <0.05); in 5th age subgroup the situation was the opposite- the duration of intensive care unit stay in group II was in 1.4 times more in group I (p <0.05). Thus, obtained data demonstrated the results of the use of personalized management of hemodynamic disorders in children with acute respiratory failure. The use of a multiparametric approach to hemodynamic assessment in clinical practice may allow more differentiated use of volume replacement therapy as loop diuretics and will have a beneficial effect on the final clinical outcomes in patients with acute respiratory failure.